Empowering Scholars: Enhancing Scientific Writing Competence in State Administration Studies at UIN Sultan Syarif Kasim Riau - Erdayani, Rizki; Afandi, Muslim; Afandi, Syed Agung (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This activity aims to improve the ability of State Administration Study Program students at UIN Sultan Syarif Kasim Riau to write scientific papers. The main problem underlying this activity is students' limited understanding and skills in writing scientific articles, especially in paraphrasing, making quotations, and reference management. To overcome this problem, assistance is provided in writing scientific articles using paraphrasing techniques (manual paraphrasing and using tools), citation techniques, and the use of the reference manager application (Mendeley). In this activity, the service team collaborated with the State Administration Student Association of UIN Sultan Syarif Kasim Riau. Based on the initial assessment, not all participants were proficient in paraphrasing, making quotations, and reference management. After carrying out this service activity, all participants were able to paraphrase sentences, quote, and use reference management applications. This activity ended with the creation and publication of a Mendeley manual book on the website of the Faculty of Economics and Social Sciences, UIN Sultan Syarif Kasim Riau, so that it could provide widespread benefits.